The Trade and Welfare Consequences of U.S. Export-Enhancing Tax Provisions - Tokarick, Stephen (IMF Working Papers; Working Paper, 1994)
The U.S. tax code contains two provisions that encourage exports by reducing the U.S. corporate income tax on export profits. An applied general equilibrium model of the U.S. economy is used to estimate the trade and welfare consequences of eliminating both tax provisions. We find that the provisions ameliorate the trade-discouraging effects of U.S. tariffs, but they also adversely affect the U.S. terms of trade to such an extent that eliminating them is likely to improve U.S. domestic welfare. While it is possible to find a 'equivalent' tariff rate that replicates the effects on trade flows of removing the tax provisions, the welfare effects of a tariff differ importantly because a tariff interacts differently than the tax provisions with other distortions in the model.